A comparative examination of the conventional and rheological characteristics of crumb rubber modification produced in both laboratory and industrial settings - Kok, Baha Vural; Yetkin, Zulfu; Ozdemir, Ahmet Munir (Springer, 2025)
In asphalt production facilities, CR modification is executed through various techniques, which may involve either single or multiple passes utilizing mixing equipment and mills. Laboratory-based CR modification employs different mixing apparatus, varying speeds, durations, and temperatures, and is conducted on a smaller scale than plant operations. The degree to which laboratory mixing replicates the processes used in plant is crucial for the design of effective pavement solutions. This research aimed to evaluate the utilization of CR additive in both laboratory and plant. Enhanced binder performance was achieved in the laboratory by increasing both the mixing speed and duration. Specifically, mixing conditions of 4000 rpm for 60-90 min resulted in a binder exhibiting improved elastic properties due to effective CR-bitumen interaction. Notable differences in rheological characteristics were observed between the CR-modified binders produced in the laboratory and those generated in the plant. It was concluded that the performance of the binder produced in the plant could be replicated in the laboratory at lower speeds of 1000-2000 rpm with a mixing duration of approximately 30 min. Furthermore, to enhance the performance of the plant-produced binder, it is essential to maintain a high number of passes through the mill.
Keywords: Bitumen; Modification; Plant facility; High-shear mixer; Performance